Developing a targeting system for bacterial membranes: measuring receptor-phosphatidylglycerol interactions with 1H NMR, ITC and fluorescence correlation spectroscopy. Issue 2 (6th November 2014) - Alliband, Amanda; Wang, Zifan; Thacker, Christopher; English, Douglas S.; Burns, Dennis H.
Abstract : We report the development of a potential targeting system for bacterial membranes containing phosphatidylglycerol. Abstract : An ammonium picket porphyrin that targets bacterial membranes has been prepared and shown to bind to phosphatidylglycerol (PG), a bacterial lipid, when the lipid was in solution, contained within synthetic membrane vesicles, or when in Gram-negative and Gram-positive bacterial membranes. The multifunctional receptor was designed to interact with both the phosphate anion portion and neutral glycerol portion of the lipid headgroup. The receptor's affinity and selectivity for binding to surfactant vesicles or lipid vesicles that contain PG within their membranes was directly measured using fluorescence correlation spectroscopy (FCS). FCS demonstrated that the picket porphyrin's binding pocket was complementary for the lipid headgroup, since simple Coulombic interactions alone did not induce binding. 1 H NMR and isothermal titration calorimetry (ITC) were used to determine the receptor's binding stoichiometry, receptor–lipid complex structure, binding constant, and associated thermodynamic properties of complexation in solution. The lipid–receptor binding motif in solution was shown to mirror the binding motif of membrane-bound PG and receptor. Cell lysis assays with E. coli (Gram-negative) and Bacillus thuringiensis (Gram-positive) probed with UV/Visible spectrophotometry indicated that the receptor was able to penetrate either bacterial cell wall and to bind to the bacterial inner membrane.